Pattern of facial nerve palsy during parotidectomy: a single-center experience - Abdulwahid M. Salih; Hiwa O. Baba; Yadgar A. Saeed; Aso S. Muhialdeen; Fahmi H. Kakamad; Shvan H. Mohammed; Zuhair D. Hammood; Karzan M. Salih; Rawezh Q. Salih; Dahat A. Hussein; Hunar A. Hassan (Journal of International Medical Research, 2022)
Objective This study was performed to report and analyze the prevalence of permanent facial nerve paralysis following parotidectomy for various benign and malignant lesions in a single center. Methods This single-center retrospective study included all patients who underwent parotidectomy (total and superficial) for benign and malignant tumors and chronic inflammatory diseases during a 6-year period. Patients who had previously undergone an operation of the parotid gland and those with preoperative facial weakness were excluded. Results The study included 127 patients ranging in age from 14 to 83 years (median, 45.89 years). Most patients were female (n = 83, 65.4%). The most prevalent procedure was superficial parotidectomy (n = 117, 92.1%), followed by total parotidectomy (n = 6, 4.7%). The average operative duration was 138 minutes (range, 80–400 minutes). Histopathology revealed that 109 (85.8%) patients had benign tumors, 14 (11.0%) had malignant tumors, and 4 (3.1%) had chronic sialadenitis. Only two patients sustained an injury to the cervical branch of the facial nerve. Conclusion In this single-center experience of parotid surgery, the rates of transient and permanent facial paralysis were acceptably low at 9.0% and 1.6%, respectively, for all pathologies.